2003
DOI: 10.1063/1.1580195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg accumulation on chemical and electronic properties of Mg-doped p-type GaN surface

Abstract: Chemical and electronic properties of Mg-doped p-GaN surfaces were systematically investigated by x-ray photoelectron spectroscopy ͑XPS͒ and Auger electron spectroscopy ͑AES͒. The doping density of Mg ranged from 3ϫ10 19 to 9ϫ10 19 cm Ϫ3 . The XPS and AES analyses revealed the accumulation of Mg for all the air-exposed and chemically treated p-GaN surfaces. The apparent density of Mg calculated from the XPS integrated intensity and the AES intensity was more than one order higher than the value in bulk determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Consequently, the reduction of E F À E V in the nearsurface region, as shown in Fig. 2c, can be directly correlated to the reduction in the downward surface band bending with increasing Mg-dopant incorporation 30,31 . In addition, our detailed analysis reveals that variations in the surface band bending have a very small, or negligible dependence on the morphology of GaN nanowires.…”
Section: Structuralmentioning
confidence: 84%
“…Consequently, the reduction of E F À E V in the nearsurface region, as shown in Fig. 2c, can be directly correlated to the reduction in the downward surface band bending with increasing Mg-dopant incorporation 30,31 . In addition, our detailed analysis reveals that variations in the surface band bending have a very small, or negligible dependence on the morphology of GaN nanowires.…”
Section: Structuralmentioning
confidence: 84%
“…Auger emission shoulders seen in Fig. 4(b) are the evidence Ga rich state [24]. emission seen at 3.47 eV originates from a region of pure GaN at the tip of the nanorod, where the optical quality of the hexagonal nanorod is superior to that seen in the base region (exciton bound to a neutral donor, D 0 X).…”
Section: Structural and Elemental Characterizationsmentioning
confidence: 88%
“…4 The doping of Mg generally exhibits strong surface segregation. 5 So far, we have obtained an unintentionally high Mg doping level in a nominally undoped top layer. Chang et al reported that the Mg concentration is mostly attributed to the memory effect, i.e., doping mechanism during the metalorganic vapor phase epitaxy ͑MOVPE͒ regrowth due to the residual Mg contamination in the reactor.…”
Section: Introductionmentioning
confidence: 99%